Sleep disturbances and upregulation of brain arousal during daytime in depressed versus non-depressed elderly subjects. (17th November 2017) - Ulke, Christine; Sander, Christian; Jawinski, Philippe; Mauche, Nicole; Huang, Jue; Spada, Janek; Wittekind, Dirk; Mergl, Roland; Luck, Tobias; Riedel-Heller, Steffi; Hensch, Tilman; Hegerl, Ulrich
Abstract: Objectives: Although patients with depression often suffer from sleep disturbances, most of them are not sleepy. Upregulation of brain arousal has been proposed as pathophysiological mechanism explaining sleep disturbances, inner tension, autonomic hyperarousal and anhedonia in depression. The aim of the current study was to examine the association between night-time sleep disturbances and brain arousal regulation the next day in depressed versus non-depressed subjects. Methods: Twenty-eight elderly subjects (21 female; age = 70.5 ± 4.4 years) with depressive syndromes without psychotropic medication, and 28 controls (22 female; age = 70.9 ± 4.5 years), underwent a 15-min resting electroencephalogram; the Vigilance Algorithm Leipzig (VIGALL 2.1) provided an objective measure of brain arousal regulation. Sleep disturbances were assessed by a validated and self-rated sleep questionnaire. Results: In the depressive group, but not in controls, more sleep disturbances were associated with a higher brain arousal stability score (high score corresponds to upregulation) the next day (sleep onset latency: r s = 0.69, P < .0001; sleep quality: r s = −0.59, P < .001). Conclusions: The data confirm the hypothesis that in persons with depressive syndromes sleep disturbances are related to upregulation of brain arousal the next day. This finding is in line with the concept that dysregulation of brain arousal is a central pathophysiological aspect in depression.